Exploring Pt-Impregnated CdS/TiO2 Heterostructures for CO2 Photoreduction - Lidia García-Santos; Javier Fernández-Catalá; Ángel Berenguer-Murcia; Diego Cazorla-Amorós (Nanomaterials)
This work focuses on the production of methane through the photocatalytic reduction of carbon dioxide using Pt-doped CdS/TiO2 heterostructures. The photocatalysts were prepared using P25 commercial titania and CdS synthesized through a solvothermal methodology, followed by the impregnation of Pt onto the surface to enhance the physicochemical properties of the resulting photocatalysts. The pure and heterostructure-based materials were characterized using X-ray diffraction (XRD), inductively coupled plasma optical emission spectroscopy (ICP-OES), scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), ultraviolet-visible spectroscopy (UV-Vis), ultraviolet photoelectron spectroscopy (UPS), and photoluminescence spectroscopy (PL). The obtained results show the successful synthesis of the heterostructure impregnated with Pt. Moreover, the observed key role of CdS and Pt nanoparticles in the final semiconductor is to reduce the electron-hole pair recombination rate by acting as an electron sink, which slows down the recombination process and increases the photocatalyst efficiency. Thus, Pt-doped CdS/TiO2 heterostructures with the best observed composition presents better catalytic activity than P25 titania with methane production values being 460 and 397 µmol CH4/g·h, respectively.